2011
DOI: 10.1111/j.1349-7006.2011.01852.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray irradiation and Rho‐kinase inhibitor additively induce invasiveness of the cells of the pancreatic cancer line, MIAPaCa‐2, which exhibits mesenchymal and amoeboid motility

Abstract: Tumor cells can migrate and invade tissue by two modes of motility: mesenchymal and amoeboid. X-ray or c-ray irradiation increases the invasiveness of tumor cells with mesenchymal motility through the induction of matrix metalloproteinases (MMP), and this increase is suppressed by MMP inhibitors (MMPI). However, the effects of X-ray or c-ray irradiation on the invasiveness of tumor cells with amoeboid motility remain unclear. We investigated the effect of irradiation on amoeboid motility by using cells of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 35 publications
5
48
0
Order By: Relevance
“…The data from the literature concerning irradiation effects on migration and invasion are controversial depending on tumor entity. Some authors detected an irradiation-induced increase in migration and invasion in glioma and pancreatic cell lines, 12,13 while other authors found an irradiation-induced decrease in lung adenocarcinoma, colorectal carcinoma or sarcoma cell lines. 4,9,16 However, the detected differences between individual melanoma cell lines in irradiation-induced changes in metastasis-relevant properties as well as in Eph/ephrin expression seem to base rather on genetic or epigenetic background than on origin of the cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from the literature concerning irradiation effects on migration and invasion are controversial depending on tumor entity. Some authors detected an irradiation-induced increase in migration and invasion in glioma and pancreatic cell lines, 12,13 while other authors found an irradiation-induced decrease in lung adenocarcinoma, colorectal carcinoma or sarcoma cell lines. 4,9,16 However, the detected differences between individual melanoma cell lines in irradiation-induced changes in metastasis-relevant properties as well as in Eph/ephrin expression seem to base rather on genetic or epigenetic background than on origin of the cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, an irradiation-induced increase in substrate adhesion was demonstrated for mouse melanoma, fibrosarcoma cells and lung cancer. 2,[8][9][10][11] Furthermore, irradiation was found to increase motility, migration and invasion in glioma, pancreatic cancer, non-small-cell lung cancer 8,[11][12][13] and also to increase metastasis in vivo. 10,14,15 Further, increasing migration at low doses has been described, followed by a decrease at higher doses.…”
Section: Introductionmentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 3 In cancer, carbon (C)-ion irradiation has advantages over conventional photon therapy, such as accurate dose distribution and enhanced biological effects due to higher linear energy transfer (LET) translated into two-to three-fold higher cytotoxicity as evidenced by the analysis of biological endpoints, including cell death, DNA damage, and chromosomal aberrations (1,2).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Radiotherapy has been found to promote the invasion of various kinds of cancer cells including GBM [5][6][7][8][9]. Ionizing radiation (IR) activates multiple signalling pathways in tumour cells, which modulate several cellular functions and induce the secretion of growth factors and chemokines, resulting in increased migration and invasiveness of cancer cells [10][11][12].…”
mentioning
confidence: 99%